One Welfare – a platform for improving human and animal welfare. (22nd October 2016) - Pinillos, R. García; Appleby, M. C.; Manteca, X.; Scott‐Park, F.; Smith, C.; Velarde, A.
Abstract : Adopting the concept of One Welfare could help to improve animal welfare and human wellbeing worldwide, argue Rebeca García Pinillos, Michael Appleby, Xavier Manteca, Freda Scott‐Park, Charles Smith and Antonio Velarde